VALIDATION OF CORROSION STATUS OF SOME ROOFING SHEETS UTILIZED IN GOMBE METROPOLIS - Usman, Y. M.; Mohammed, A. B.; Muzakir, M. M.; Madaki, L. A.; Modibbo, U. U. (FUDMA JOURNAL OF SCIENCES, 2024)
The study was aim at investigation the level of corrosion on roofing sheets utilized in Gombe where acid and alkaline medium immersion test of 25 days showed that light zinc (0.15 mm) sample decreased in weight from 0.03g to 0.04 g while the 2.0mm zinc decreased in weight range of 0.01g to 0.04 g in the alkaline solution. Samples of thick aluminum (5.5 mm) and light aluminium(4.5mm) showed insignificant weight range 0.0g to 0.03 g after immersion in alkaline. In acidic medium both light and thick zinc showed greater weight lost 0.05g to 0.08g. However both the thick and light aluminium showed loss of their shiny appearance only with no renowned significant corrosion throughout the twenty-five days of immersion. XRF analysis of the oxides on the corrosion samples of 0.15mm zinc showed decreasing pattern of: Fe2O3 > SiO2.> Na2O >Al2O3 > MnO > CaO respectively. The decreasing order of the percentage of oxides on 2.0mm zinc: Fe2O3 > SiO2 .>Al2O3 > CaO > MnO oxides on 4. 5mm. Aluminium is in decreasing order of; Al2O3 > SiO2.> Fe2O3 > CaO > K2O . On the other side percentage of the oxides of 5.0mm Aluminium is Al2O3 > SiO2 > MnO respectively. Aluminium samples are more durable and resistant which indicates suitability for roofing than zinc sheets.